The impact of time slot management systems on drivers' working hours in logistics service providers' enterprises - Bilonoh, Oksana; Halak, Iryna; Ovchar, Denys (Management and Entrepreneurship: Trends of Development, 2025)
The research is dedicated to analyzing the key aspects of efficient use of drivers' working hours in logistics providers, specifically the issue of delays during loading and unloading at customer warehouses. Rational use of drivers' working hours is an important factor in increasing the productivity of logistics companies and reducing costs associated with vehicle downtime. The purpose of the study is to justify the necessity of implementing a Time Slot Management system (TSMS) to minimize delays and improve resource utilization efficiency in transport companies.The subject of the research is the process of managing drivers' working hours in logistics operations. The methods of systems analysis, mathematical modeling, and comparative analysis were applied in the study. An analysis of existing approaches to organizing loading and unloading processes was conducted, and the main factors influencing delays were identified.The introduction of a Time Slot Management system is proposed to reduce waiting times, increase resource utilization efficiency, and minimize vehicle downtime. Particular attention is paid to the use of Estimated Time of Arrival (ETA) for accurate forecasting of driver arrival times and quick response to schedule deviations.Different driver behavior scenarios based on time slot management models are described, allowing the strategy to be adapted to the characteristics of warehouses and customer requirements. The proposed scientific statements contribute to the development of logistics process management theory by improving the time slot planning system in transport logistics.The practical significance of the work lies in the possibility of applying the developed recommendations in the activities of logistics providers to improve the organization of drivers' work, reduce delays, and increase the efficiency of transport resource utilization.JEL класифікатор: L91, J22, O33, J81